2008
DOI: 10.1097/01.aog.0000296488.85807.b3
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Compared With Conventional Cervical Cytology

Abstract: Liquid-based cervical cytology is neither more sensitive nor more specific for detection of high-grade cervical intraepithelial neoplasia compared with the conventional Pap test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
240
6
24

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 400 publications
(288 citation statements)
references
References 46 publications
18
240
6
24
Order By: Relevance
“…Earlier publications found an increased detection rate of HSIL as summarized in several reviews. [5][6][7] More recently, some HTAs and systematic reviews 8,11,12 using stringent criteria did not show superiority of LBC over CC. Additionally, two recent large randomized studies, which were situated within organized screening programs did not observe a higher relative sensitivity of LBC for histologically confirmed CIN compared with CC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier publications found an increased detection rate of HSIL as summarized in several reviews. [5][6][7] More recently, some HTAs and systematic reviews 8,11,12 using stringent criteria did not show superiority of LBC over CC. Additionally, two recent large randomized studies, which were situated within organized screening programs did not observe a higher relative sensitivity of LBC for histologically confirmed CIN compared with CC.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Health technology assessments (HTA) and meta-analysis reviews as well as two recent, large randomized trials which were conducted in the context of organized screening programs did not find a higher sensitivity of LBC for the detection of cervical intraepithelial neoplasia grade 2 and higher (CIN2þ). [8][9][10][11][12] LBC has advantages such as faster reading of slides, fewer unsatisfactory specimens, and the possibility to use residual liquid sample for testing of Human Papillomavirus (HPV) and other molecular markers. 9,11,13,14 A disadvantage is the higher cost of LBC.…”
mentioning
confidence: 99%
“…LBP is an alternative technique for transferring the cellular material collected from the transformation zone of the uterine cervix. In contrast to CPS, the cells are not directly spread on a slide, but rather into a vial containing fixative liquid (Arbyn et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the cervical programme therefore relies on multiple opportunities at identifying and treating CIN. The use of liquid based cytology (LBC) has shown a reduction in the number of inadequate smears, but a recent systematic review and meta-analysis by Arbyn et al found that LBC did not improve the detection of high grade CIN and that LBC was neither more sensitive nor specific than conventional cytology [3].…”
Section: Introductionmentioning
confidence: 99%